1989
DOI: 10.1093/jn/119.11.1574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lipids and Vitamin E on in Vitro Lipid Peroxidation in Rat Liver and Kidney Homogenates

Abstract: Rats were fed for 5 wk 10% (wt/wt) menhaden oil (MO) or a 10% corn oil-lard (COL) mixture (1:1) in diets with a low vitamin E content (less than or equal to 5 mg/kg) or supplemented with d-alpha-tocopheryl succinate to a total of 30 or 150 mg per kg. Thiobarbituric acid-reactive substances (TBARS), conjugated dienes (CD), hexanal and total volatiles (TOV) were measured in tissue homogenates incubated at 37 degrees C for 1 h in the absence (uninduced) and presence of 15 microM ferrous sulfate (induced). The fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…However, the pentane production originating from n-6 fatty acids was considerably higher in the deficient group fed linoleic acid. Comparable results have been obtained earlier in vitamin E-deficient rats fed corn oil or menhaden oil (19). TBA-reactive substances arising mainly from n-3 fatty acids were 1.38 times higher, when the rats received menhaden oil .…”
Section: Discussionsupporting
confidence: 77%
“…However, the pentane production originating from n-6 fatty acids was considerably higher in the deficient group fed linoleic acid. Comparable results have been obtained earlier in vitamin E-deficient rats fed corn oil or menhaden oil (19). TBA-reactive substances arising mainly from n-3 fatty acids were 1.38 times higher, when the rats received menhaden oil .…”
Section: Discussionsupporting
confidence: 77%
“…Administration of fish oil to mice increased the contents of n-3 PUFA in the liver. Hu et al 47) and Leibovitz et al48) also reported similar extents of increase of PUFA contents in the liver of rats fed a fish oil-supplemented diet. Further increases of the contents of n-3 PUFA were observed in the liver of the FO+TP group in this study.…”
Section: Analysesmentioning
confidence: 67%
“…Under normal physiological conditions, the concentrations of lipid peroxides in the tissues are low. Hu et al, [29] reported elevated levels of lipid peroxides in the plasma of diabe tic rats. Lipid peroxide-mediated tissue damage results in the development of both type I and type II diabetes.…”
Section: Discussionmentioning
confidence: 99%